The Great White North Encounters September 11: Race, Gender, and Nation in Canada's National Daily, “The Globe and Mail” - Jiwani, Yasmin (Social justice, 2005)
Terror is a feature of the symbolic order, the vast mesh of representations and narratives both official and unofficial, public and private, in which a culture works out its sense of itself. It affects that dynamic but relatively stable set of implicit parameters that establish a group's sense of the actual and the possible and create a loose but definite sense of collective identity.—Geoffrey Gait Harpham (2002:573) Reprinted by permission of the publisher.